TNFα: TNFR1 signaling inhibits maturation and maintains the pro-inflammatory programming of monocyte-derived macrophages in murine chronic granulomatous disease - Gibbings, Sophie L.; Haist, Kelsey C.; Redente, Elizabeth F.; Henson, Peter M.; Bratton, Donna L. (Frontiers in Immunology, 2024)
Introduction Loss of NADPH oxidase activity results in proinflammatory macrophages that contribute to hyperinflammation in Chronic Granulomatous Disease (CGD). Previously, it was shown in a zymosan-induced peritonitis model that gp91phox-/- (CGD) monocyte-derived macrophages (MoMacs) fail to phenotypically mature into pro-resolving MoMacs characteristic of wild type (WT) but retain the ability to do so when placed in the WT milieu. Accordingly, it was hypothesized that soluble factor(s) in the CGD milieu thwart appropriate programming. Methods We sought to identify key constituents using ex vivo culture of peritoneal inflammatory leukocytes and their conditioned media. MoMac phenotyping was performed via flow cytometry, measurement of efferocytic capacity and multiplex analysis of secreted cytokines. Addition of exogenous TNFα, TNFα neutralizing antibody and TNFR1-/- MoMacs were used to study the role of TNFα: TNFR1 signaling in MoMac maturation. Results More extensive phenotyping defined normal MoMac maturation and demonstrated failure of maturation of CGD MoMacs both ex vivo and in vivo. Protein components, and specifically TNFα, produced and released by CGD neutrophils and MoMacs into conditioned media was identified as critical to preventing maturation. Exogenous addition of TNFα inhibited WT MoMac maturation, and its neutralization allowed maturation of cultured CGD MoMacs. TNFα neutralization also reduced production of IL-1β, IL-6 and CXCL1 by CGD cells though these cytokines played no role in MoMac programming. MoMacs lacking TNFR1 matured more normally in the CGD milieu both ex vivo and following adoptive transfer in vivo. Discussion These data lend mechanistic insights into the utility of TNFα blockade in CGD and to other diseases where such therapy has been shown to be beneficial.